Evaluation of IL-1Î² and TNF-Î± expression and periodontitis under the influence of orthodontic appliances with minocycline - Zhang, Jingjing; Qi, Suqing; Chen, Weican; Liu, Lin; Hui, Hongwei (Cellular and Molecular Biology, 2020)
The current experiment was carried out to observe and analyze the effects of three orthodontic appliances combined with minocycline on periodontitis and inflammatory factors of gingival crevicular fluid. the patients included in this study were 180 patients with dental crowding treated in our hospital. They were divided into three groups, namely the invisible orthodontic appliance group (n=60), self-ligation orthodontic appliance group (n=60), traditional ligation bracket group (n=60), all of which were applied with minocycline therapy. The therapeutic effects of the three groups were observed. after three months of treatment, the periodontal index of each group showed an upward trend (p<0.05). At six months to one year, the periodontal index of the self-ligation orthodontic appliance group and conventional ligation bracket group was higher than that of the invisible orthodontic appliance group, p<0.05. After treatment, the expression of IL-1Î² and TNF-Î± increased for the three groups, p<0.05; the self-ligation orthodontic appliance group and the traditional ligation bracket group were the same as the invisible orthodontic appliance group in at 24 months, p>0.05. in the early stage of orthodontic treatment, the invisible orthodontic appliance can keep the oral cavity in a clean and hygienic state. However, after 18 months of orthodontic treatment, all three orthodontic treatments did not have a significant impact on oral hygiene.